Impact of Job Satisfaction on Employee Performance at Solok Regency Transportation Department - Farhan Hidayatul Fajri; Afni Yeni; Seflidiana Roza (CV. Proaksara Global Transeduka, 2025)
The goal of this research is to examine how leadership, motivation, and job satisfaction impact the performance of employees at the Transportation Department (DISHUB) Office of Solok Regency. The research object consists of DISHUB employees located at Jl. Raya Koto Baru, Solok Regency, West Sumatra. Quantitative research was employed in the study, which involved distributing questionnaires to 92 employees for data collection. Findings from the research indicate that there is no substantial impact of leadership on employee performance, as evidenced by a t-value of 1.294 and a significance level of 0.200. Motivation also does not have a significant effect, with a t-value of -1.873 and significance of 0.065. Conversely, job satisfaction significantly influences employee performance, with a t-value of 2.060 and significance of 0.043. Simultaneously, the three variables influence employee performance with an F-value of 3.230 and significance of 0.027. The impact of leadership, motivation, and job satisfaction accounts for 11.9% of the variation in employee performance, with the remaining percentage being attributed to various other factors. This study provides recommendations to improve employee job satisfaction to enhance performance in the agency.